BENEFITS OF INTERNATIONAL PORTFOLIO DIVERSIFICATION GIVEN INCREASINGLY INTEGRATED GLOBAL STOCK MARKETS - Osinowo, Adenike.A (2009)
In this dissertation we examine the stock market indices of seven developed countries and seven emerging countries, as well as nine industry returns indices of each of the fourteen countries. This is sub-divided into before subprime crisis period (January 1995 - July 2007) and subprime crisis period (August 2007 - July 2009), to determine whether there are benefits to be gained by investors from international portfolio diversification especially during global bearish cycles when diversification is needed the most.